EFEKTIFITAS PROGRAM SYAR’I: HAFALAN ALQURAN DENGAN MENGGUNAKAN METODE ONE DAY THREE LINES PADA SISWA MTsN 01 LIMAPULUH KOTA - MAIMORI, ROMI (JURIS (Jurnal Ilmiah Syariah), 2016)
This study was inspired by the reality that memorizing the Quran had become an activity which was avoided by most of students and uninteresting as well due to its ineffectiveness of the memorizing methods. Dealing with the phenomena, this study aimed at figuring out how One Day Three Lines method was applied di MTsN 01 Limapuluh Kota, and related factors that supported or inhibited the implementation of the method in memorizing the Quran. This study belonged to descriptive quantitative design employing evaluative model of CIPP (Contexs, Input, Proses dan Produc) Method. The data were collected through participant observation, in depth interview, questionnaire, and documentation. Data analysis were carry out by checking data trustworthiness obtained from observation, interview, documentation to figure out the context and product evaluations of  One Day Three Lines memorizing method. Questionnaire was used to assess respondents’ attitude toward the method. The findings showed that One Day Three Lines memorizing method applied in MTsN 01 Lima Puluh Kota was categorized effective with an average percentage was 71.9%